(untitled) (translation. a transdisciplinary journal, 2021)
The intellectual context of the research symposium lies in the effort of modern translation studies to come to grips with a fundamental shift in our understanding of what constitutes translation and where translation locates itself in the vase range of human cognition and behavior. Long gone are rhe rimes when translation amounted to a simple exchange of words and phrases across languages; long gone too is the always questionable perception that rranslarion limited itself co literary or technical works.